2011
DOI: 10.1210/me.2010-0232
|View full text |Cite
|
Sign up to set email alerts
|

C/EBPβ Mediates Growth Hormone-Regulated Expression of Multiple Target Genes

Abstract: Regulation of c-Fos transcription by GH is mediated by CCAAT/enhancer binding protein β (C/EBPβ). This study examines the role of C/EBPβ in mediating GH activation of other early response genes, including Cyr61, Btg2, Socs3, Zfp36, and Socs1. C/EBPβ depletion using short hairpin RNA impaired responsiveness of these genes to GH, as seen for c-Fos. Rescue with wild-type C/EBPβ led to GH-dependent recruitment of the coactivator p300 to the c-Fos promoter. In contrast, rescue with C/EBPβ mutated at the ERK phospho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 69 publications
1
20
0
Order By: Relevance
“…22 Moreover, Cui et al 30 showed that growth hormone, which is a stimulator of hepatic gluconeogenesis, significantly increases BTG2 via the C/EBP-CREB pathway in adipocytes, suggesting that BTG2 may be involved in hepatic gluconeogenesis, consistent with a previous report. A recent report suggests that liraglutide, a GLP-1 agonist, increases the ATP/AMP ratio, which in turn inhibits AMP-activated protein kinase.…”
Section: Discussionsupporting
confidence: 83%
“…22 Moreover, Cui et al 30 showed that growth hormone, which is a stimulator of hepatic gluconeogenesis, significantly increases BTG2 via the C/EBP-CREB pathway in adipocytes, suggesting that BTG2 may be involved in hepatic gluconeogenesis, consistent with a previous report. A recent report suggests that liraglutide, a GLP-1 agonist, increases the ATP/AMP ratio, which in turn inhibits AMP-activated protein kinase.…”
Section: Discussionsupporting
confidence: 83%
“…hBD-2-induced ERK or JNK might promote IL-22 or oncostatin M production, respectively. It is reported that ERK activates Sp1 and C/EBP by inducing their phosphorylation and/or expression (Chanteux et al 2007;Cui et al 2011;Lue et al 2011), while JNK activates AP-1 via phosphorylation and/or expression of AP-1 components like c-Jun (Lue et al 2011). Thus, hBD-2-induced ERK or JNK could activate Sp1/C/EBP or AP-1 to promote IL-22 or oncostatin M expression, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Exquisitely sensitive to a wide range of extracellular stimuli, CCN1 is transcriptionally activated by platelet-derived growth factor and fibroblast growth factor 2 [8], transforming growth factor β1 (TGF-β1) [19], growth hormone [20], the phorbol ester 12- O -tetradecanoylphorbol-13-acetate, cAMP [8], vitamin D 3 [21], estrogen and tamoxifen [22], angiotensin II [23,24], hypoxia [25], UV light [26], and mechanical stretch [27,28]. Consistent with a role in inflammation, CCN1 is also induced by bacterial and viral infections [2932], and by inflammatory cytokines such as interleukin-1 (IL-1) and tumor necrosis factor α (TNF-α) [33].…”
Section: Transcriptional and Post-transcriptional Regulationmentioning
confidence: 99%